Corrosion resistance of niobium-added slag-free self-shielded flux-cored welding overlay in neutral solution. Issue 15 (13th October 2022) - Liu, Dashuang; Wei, Ping; Wu, Yucheng; Long, Weimin; Wang, Rui
ABSTRACT: The niobium-added iron-based slag-free self-shielded flux-cored wire was developed and the effect of niobium addition on the corrosion resistance in neutral pH solution was investigated. The carbides, including NbC carbides, primary (Cr, Fe)7 C3, and eutectic (Cr, Fe)3 C carbides, remain intact after neutral corrosion, but the grain interface is corroded preferably for all the niobium-added welding overlays. The eutectic microstructure of 7.2 wt-% niobium-added welding overlay, which has more grain interface, leads to severe corrosion. When niobium addition reaches 14.4 wt-%, the welding overlay possesses the best corrosion resistance since more NbC carbides are formed, prophase austenite dendrite is precipitated, decreasing the grain interface, and chromium content is increased in the matrix of the hypoeutectic microstructure.